Single Particle Level Density in a Harmonic – Oscillator Potential Well - Jasim, Mahdi Hadi (Iraqi Journal of Physics, 2011)
The purpose of this paper is to study the properties of the partial level density ( ) l g and the total level density g ( ), numerically obtained as a l sum of ( ) l g up to 34 max l  , for a Harmonic – Oscillator potential well. This method applied the quantum – mechanical phase shift technique and concentrated on the continuum region. Also a discussion of peculiarities of quantal calculation for single particle level density of energy – dependent potential